2016 Rio Olympics: an epidemiological study of the men`s and women`s Rugby-7s tournaments - Fuller, C. W.; Taylor, A.; Raftery, M. (British Journal of Sports Medicine, 2017)
Objective: To determine the incidence, severity and nature of injuries sustained during the men`s and women`s 2014/2015 and 2015/2016 Sevens World Series (SWS) and 2016 Olympic Games Rugby Sevens tournaments.